PENGEMBANGAN SISTEM INFORMASI PELAYANAN KLINIK GIGI PRAKTIK BERSAMA SAWOJAJAR MALANG - Adnan Zulkarnain; Putri Auliya Rahmah Belladina Maurieftha (Program Studi Pendidikan Informatika, Universitas Citra Bangsa, 2023)
The current use of information systems significantly supports data management efficiency, especially in healthcare administration and services. Although some dental clinics, such as Praktik Bersama Sawojajar Malang, still rely on manual approaches to patient administration and record-keeping, efforts are needed to enhance service quality. Therefore, this research aims to develop a web-based information system to streamline medical administration processes. This study employs a qualitative research method with a case study approach. The result is an information system encompassing patient registration, appointment scheduling, medical record keeping, payment processing, and clinic revenue calculation. This system has been successfully tested using Black Box Testing, with a 100% success rate from 50 conducted tests. Through the implementation of this information system, it is expected that Praktik Bersama Sawojajar Malang can improve operational efficiency, reduce administrative errors, and provide better services to patients.